Perancangan Website Penjualan Kebutuhan Aksesoris Game Menggunakan CMS Prestashop - Muhammad Ridho; Ina Sholihah Widiati; Tinuk Agustin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
With the current development of information technology, it adds new opportunities for actors kIt is activity buy and sell. at the same time the need for apparel gaming also increased with the development of technology. The increasing need for game accessories adds a new market share for online sales, because many consumers are lazy to come directly to physical stores. This makes the store must be able to compete for the market for game accessories through online sales.Design website e-commerce by using (Content Management System) CMS aims to see if the development is feasible to use likee-commerceanother. It takes an application that can be designed easily to be applied and understood as building a new online store.